2021
DOI: 10.1093/rb/rbab076
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite composited PEEK with 3D porous surface enhances osteoblast differentiation through mediating NO by macrophage

Abstract: The adverse immune response mediated by macrophages is one of the main factors that are prone to lead poor osseointegration of polyetheretherketone (PEEK) implants in clinic. Hence, endowing PEEK with immunomodulatory ability to avoid the adverse immune response becomes a promise strategy to promote bone repair. In this work, sulfonation and hydrothermal treatment were used to fabricate a three-dimensional porous surface on PEEK and hydroxyapatite composited PEEK. The hydroxyapatite composited PEEK with three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…However, the mechanical strength of the HA/PEEK composite materials became inferior, which is consistent with previous studies. 29 The poor mechanical strength may be attributed to the surface microstructure and internal architectural issues. 23,24,30,31 Addressing this limitation is essential to expand the range of medical applications of these materials in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanical strength of the HA/PEEK composite materials became inferior, which is consistent with previous studies. 29 The poor mechanical strength may be attributed to the surface microstructure and internal architectural issues. 23,24,30,31 Addressing this limitation is essential to expand the range of medical applications of these materials in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The authors cleared that hydrogel functional groups facilitate apatite formation in the extracellular matrix 60 . Liu et al indicated osteoblastic differentiation capacity of bone marrow mesenchymal stem cells in 3D constructions of PEEK 66 . Some studies suggested the increased osteogenic capacity of PEEK while incorporated or modified by different substances 19,22,24,48 .…”
Section: Discussionmentioning
confidence: 99%
“…(b) Expression of osteogenic-related genes. (c) Interaction of materials, macrophages, and mBMSCs ( Liu et al, 2022 ). (C) Under the presence of bacteria, the production of ROS increases SB content and macrophage activity.…”
Section: Modification For Enhanced Biopropertiesmentioning
confidence: 99%